2020
DOI: 10.3389/fonc.2020.00638
|View full text |Cite
|
Sign up to set email alerts
|

Identification Hub Genes in Colorectal Cancer by Integrating Weighted Gene Co-Expression Network Analysis and Clinical Validation in vivo and vitro

Abstract: Colorectal cancer (CRC) is the third leading cause of death in the world. However, the key roles of most molecules in CRC remain unclear. This study aimed to identify key modules and hub genes associated with the progression of CRC. The data of the patients with CRC were obtained from the Gene Expression Omnibus (GEO) database and assessed by weighted gene co-expression network analysis (WGCNA), Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses performed in R. by WGCNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Among the other genes with strong evidence of association from the BRI method, EPHA7, TTC28, EVI2B, GPC3, CENPQ, NOTCH3, and SMPDL3A were previously reported to play a role in the development and prognosis of colorectal cancer (39)(40)(41)(42)(43)(44)(45). Our study is the first to report an association of C6orf120, COL22A1, FSIP1, AKR1D1, and CEP43 specifically with colorectal cancer risk.…”
Section: Discussionsupporting
confidence: 51%
“…Among the other genes with strong evidence of association from the BRI method, EPHA7, TTC28, EVI2B, GPC3, CENPQ, NOTCH3, and SMPDL3A were previously reported to play a role in the development and prognosis of colorectal cancer (39)(40)(41)(42)(43)(44)(45). Our study is the first to report an association of C6orf120, COL22A1, FSIP1, AKR1D1, and CEP43 specifically with colorectal cancer risk.…”
Section: Discussionsupporting
confidence: 51%
“…It has been found that low expression of EVI2B could enhance cell proliferation, invasion and migration in colorectal cancer cells and remarkably promote tumor growth. besides, EVI2B participated in PPIs (protein-protein interactions) of T-cell-mediated system-wide modulation (29). Similarly, EVI2B was a potential prognostic biomarker for colorectal cancer (CRC) (30).…”
Section: Discussionmentioning
confidence: 99%
“… 51 Moreover, it has been reported that CD48 can suppress CRC progression by inhibiting the proliferation, migration, and invasion capacity of CRC cells as well as tumour growth in vivo. 52 In the present study, we mainly focused on the expression pattern of ICGs and clinical correlation in CRC, so we included these ICGs as the object. Kaplan–Meier's survival analysis confirmed that the low expression groups of IDO1, CD274, CTLA4 and CD48 had the best prognosis, while the high expression groups of IDO1, CD274, CTLA4 and CD48 had the worst prognosis.…”
Section: Discussionmentioning
confidence: 99%